Sebuah manuskrip Belanda mengenai kemalangan Armada VOC di Pulau Kabaena, Mac-Mei 1650 - Horst H. Liebner, (Universiti Kebangsaan Malaysia, 2007)
In the 17th and 18th centuries, accounts of remarkable voyages, expeditions and shipwrecks in the Eastern and Western Seas were very much in vogue, and hundreds of books and pamphlets of this genre are known. Surprisingly, the mishap of the Ternatan Fleet of 1650 did not receive much attention. We know only of some scattered annotations concerning the event. Fortunately, a copy of the journal kept by the Breede Raadt, the ‘Assembly of the Leaders of the Fleet’, is preserved in the National Archives of the Netherlands, registered as Copie daghregister gehouden bij d’opperhoofden der verongeluckte schepen Tijger, Bergen op Zoom, Aechtekercke, Luijpaert ende de fluijt de Juffrouw op ‘t eijlandeken Sagorij omtrent Bouton 23 Februarij tot 28 Maij 1650, Fonds Code 1.04.02, Item no.1179A/B, Section page number 296-340. This author consulted and copied the microfilm version of this journal and gives particular attention to the relations between the Dutch shipwrecks, the local population and the Buton Sultanate. This paper understands itself as a vestige for further research into this matter. Ideally, the Stranding of the Ternatan Fleet of 1650 can become the subject for an integrated study by philologists, historians and archaeologists of East and West alike. Clearly, the accident resulted in what was probably the first chronicled ‘long-term residence’ of Western people on the Butonese Islands, and the journal of the accident proves most valuable for our knowledge about Buton in the 17th century history and ethnography. One even wonders whether local chronicles contain an indigenous version of the event. Likewise, the wreck site itself may deepen our insights about European shipping of the 17th century. Last but not least, the incident ‘as such’ throws light on an era that too often is overlooked in the writing of both European and Asian history. Thus, the mutual co-operation that coloured the event 355 years ago may eventually to contemporary research